Implementasi Generate Map dan Pemunculan Objek secara Acak pada Game 3D menggunakan Bahasa C# dan Metode Perlin Noise di Unity: Studi Kasus pada Game Development - Renita Selviana; Dauw Bastha Fiastat Lugata; alimin alimin (SPIRIT, 2023)
Perlin noise algorithm is used to generate noise on the map surface, creating natural effects in 3D games. In this research, a C# script code has been implemented in Unity that can generate maps and spawn random objects in the game. The research results demonstrate that the implementation of map generation and random object spawning techniques can enhance gameplay quality and provide a more immersive playing experience for users. This research aims to contribute to game development on the Unity platform as well as the development of map This research explores the implementation of procedural content generation (PCG) techniques using C# programming language and Perlin noise method in Unity to generate map and random object spawning in 3D games. The main objective of this research is to develop PCG techniques that can be applied to game development. The generation and random object spawning techniques in 3D games using Perlin noise method.